Synthesis and Structural Studies of Bidentate Schiff Bases and Their Complexes with Cu(II), Ni(II), Co(II), Cd(II) and Zn(II) - POYRAZ, MEHMET; YENIKAYA, CENGIZ; TOLGA COLAK, ALPER (Asian Journal of Chemistry, 2010)
Novel Schiff bases prepared by condensation of substituted aniline with aldehydes as [NO] chelating bidentate ligands have been characterized by their elemental analysis, IR and electronic spectra. Their complexes of Cu(II), Ni(II), Co(II), Cd(II) and Zn(II) ions have been synthesized and characterized with the spectroscopic methods, magnetic susceptibility and elemental analysis. The results indicate that metal ions coordinate with azomethine nitrogen atoms and phenolic oxygen atoms of ligands. The mole ratio of ligands and metal ions in the complexes has been determined to be 2:1, according to the results of elemental analysis. All complexes have been considered in four coordinated configurations. While Cu(II) complexes had square-planar configuration, the others possessed tetrahedral geometries. The TG and DTA properties of compounds have been studied.